From placement to prison revisited: Do mental health services disrupt the delinquency pipeline among Latino, African American and Caucasian youth in the child welfare system?. (December 2015) - Garcia, Antonio R.; Greeson, Johanna K.P.; Kim, Minseop; Thompson, Allison; DeNard, Christina
Abstract: Racial and ethnic disparities in delinquency among child welfare-involved youth are well documented. However, less is known about the mechanisms through which these disparities occur. This study explores the extent to which sets of variables predict the occurrence of juvenile delinquency and whether race/ethnicity moderates the strength of the relationships between (1) social, emotional, and behavioral (SEB) problems and delinquency and (2) mental health service use and delinquency. We used a nationally representative sample of 727 African American, Caucasian, and Latino youth between the ages of 12–17 who were referred to the child welfare system. Controlling for age, gender, placement instability, maltreatment history, poverty, and urbanicity, linear regression analyses revealed that African American and Latino youth engaged in more delinquent acts than Caucasian youth did. However, service use decreased the likelihood of engaging in more delinquent acts for African Americans. Additional efforts are needed to illuminate and address the contextual and organizational barriers to delivering effective mental health services as a strategy to reduce racial disparities in delinquent behavior.